Chloroquine enhances the efficacy of cisplatin by suppressing autophagy in human adrenocortical carcinoma treatment - Qin L; Xu TY; Xia LL; Wang XJ; Zhang X; Zhang XH; Zhu ZW; Zhong S; Wang CD; Shen ZJ (Dove Medical Press, 2016)
Liang Qin,1,* Tianyuan Xu,1,* Leilei Xia,1 Xianjin Wang,1 Xiang Zhang,1 Xiaohua Zhang,1 Zhaowei Zhu,1 Shan Zhong,1 Chuandong Wang,2 Zhoujun Shen1 1Department of Urology, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, 2Key Laboratory of Stem Cell Biology, Shanghai Institutes for Biological Sciences, Chinese Academy of Sciences, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China *These authors contributed equally to this work Background: It has been demonstrated that chloroquine (CQ) enhances the efficacy of chemotherapy. However, little is known about whether CQ could enhance the efficacy of cisplatin (DDP) in the treatment of adrenocortical carcinoma (ACC). In this study, we explore the efficacy and mechanism by which CQ affects DDP sensitivity in human ACC in vitro and in vivo.Methods: The autophagic gene Beclin-1 expression was detected by immunohistochemistry, and the protein levels were analyzed using immunoblotting assays of ACC tissues and normal adrenal cortex tissues. The ACC SW13 cells were treated with DDP and/or CQ. The cell viability assay was performed using the MTT method. Qualitative autophagy detection was performed by monodansylcadaverine staining of autophagic vacuoles. Annexin V-fluorescein isothiocyanate/propidium iodide double staining was used to count cell apoptosis by flow cytometry. The autophagy-related protein (Beclin-1, LC3, and p62) and apoptosis relative protein (Bax and Bcl-2) levels were evaluated with Western blot analysis. Furthermore, a murine model of nude BALB/c mice bearing SW13 cell xenografts was established to evaluate the efficacy of concomitant therapy.Results: The expression of the autophagic gene Beclin-1 was significantly downregulated in ACC tissues compared to normal adrenal cortex tissues. The Beclin-1 protein level in ACC tissues was lower than that in normal adrenal cortex tissues (P<0.05). In vitro concomitant therapy (DDP and CQ) was more effective in restraining SW13 cell proliferation. DDP could promote cell apoptosis and induce autophagy in SW13 cells. Concomitant therapy further promoted cell apoptosis by inhibiting autophagy. In vivo, we found that concomitant therapy was more potent than DDP monotherapy in inhibiting the growth of xenografted tumors and prolonging the survival of tumor-bearing mice.Conclusion: The antitumor ability of DDP was related to autophagy activity, and the concomitant therapy (DDP and CQ) could be an optimal strategy for treating ACC. Keywords: adrenocortical carcinoma, chloroquine, cisplatin, apoptosis, autophagy